2016
DOI: 10.1177/00333549161310s114
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Routine HIV Screening in Three Chicago Hospitals: Lessons Learned

Abstract: Objective. This study describes routine HIV screening implementation and outcomes in three hospitals in Chicago, Illinois.Methods. Retrospective data from three hospitals were examined, and routine testing procedures, testing volume, reactive test results, and linkage-to-care outcomes were documented.Results. From January 2012 through March 2014, 40,788 HIV tests were administered at the three hospitals: 18,603 (46%) in the emergency department (ED), 7,546 (19%) in the inpatient departments, and 14,639 (36%) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The low rate of routine HIV testing reflects a high rate of missed opportunities: instances where HIV-infected individuals present to medical care with possible HIV-related illnesses, but who are not tested for HIV. The prevalence of missed opportunities is generally high across various populations [ 14 , 16 19 ]. Inpatient units provide a unique opportunity for HIV recognition and linkage to long-term follow-up care.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The low rate of routine HIV testing reflects a high rate of missed opportunities: instances where HIV-infected individuals present to medical care with possible HIV-related illnesses, but who are not tested for HIV. The prevalence of missed opportunities is generally high across various populations [ 14 , 16 19 ]. Inpatient units provide a unique opportunity for HIV recognition and linkage to long-term follow-up care.…”
Section: Discussionmentioning
confidence: 99%
“…Inpatient units provide a unique opportunity for HIV recognition and linkage to long-term follow-up care. A study by Rucker et al conducted at three hospitals in Chicago, Illinois, found that inpatient areas had the highest seroprevalence of undiagnosed HIV (0.6%) compared to emergency room (0.4%) and outpatient care areas (0.1%), highlighting the need to focus on inpatient HIV screening [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are unique opportunities to test patients who visit the emergency department or urgent care but might not otherwise seek testing [4-7], and hospital-wide routine HIV screening has been shown to be a valuable tool for identifying new infections and preventing missed opportunities to diagnose individuals of unknown status [8,9]. These testing opportunities can be driven by symptoms, which may indicate acute HIV infection [10] or by the patient care situation (e.g., pregnancy) [11,12].…”
Section: Introductionmentioning
confidence: 99%